Media, politics and democracy in the 14th Malaysian General Election / Ismail Sualman, Fariza Hanis Abdul Razak and Nuurrianti Jalli - Sualman, Ismail; Abdul Razak, Fariza Hanis; Jalli, Nuurrianti
The 2018 election upset in Malaysia had intrigued scholars both local and international alike to study one of the world's bloodless government transitions. The historic date of 9 May 2018 had witnessed Malaysians of different backgrounds waited eagerly for the election results to be announced by the media. Some went to the streets to gather with like-minded people to show support for their respective preferred coalition. As the results were announced at the break of the dawn on the 10 May 2018, Malaysia became a trending topic on social media, as for the first time in history, the Barisan Nasional (National Coalition) failed to form a government, losing the election to Pakatan Harapan (Hope Alliance). Ever since 2008, Barisan Nasional (BN) as the leading political coalition in Malaysia since its formation after the racial riots in 1969 had witnessed a decline in support. The 12th general election in 2008 became the first setback in the BN government after the loss of the two-thirds majority to the opposing coalition. The then Prime Minister Ahmad Badawi had openly declared the loss was due to the rise of new media - asserted that the coalition had underestimated the Internet as a political tool. Despite numerous efforts were placed after 2008 to increase BN social media presence and tactical use of cyber troopers, BN continued to lose its dominance in the parliament in 2013. Eventually, in 2018, BN had failed to form the government in the election upset against the Pakatan Harapan (PH).